Lord of the flies - Golding, William, 1911-1993.; Faber and Faber (London : Faber and Faber, 1954)
Stranded on an island while an atomic war destroys the rest of the world, a group of young boys revert to savagery as they struggle to survive.
Young Adult
Keywords: Nuclear warfare -- Fiction; Survival -- Fiction; Survival skills -- Fiction